Clinical Characteristics and Predictive Value of the Lactate Dehydrogenase‐to‐Lymphocyte Ratio in Infants With Pneumocystis jirovecii Pneumonia: A Retrospective Study - Lilin Huang (Health Science Reports)
ABSTRACT Background and Aims Pneumocystis jirovecii pneumonia (PCP) is a life‐threatening fungal infection in immunocompromised children. The aims of this study were to observe the clinical characteristics and assess the predictive value of the lactate dehydrogenase (LDH)‐to‐total lymphocyte count ratio (LTLR) for early identification of PCP in infants under 1 year old with interstitial pneumonia. Methods We retrospectively evaluated medical data of infants with PCP and viral or Mycoplasma pneumoniae pneumonia during the period from January 1, 2016 until December 31, 2021 at Guangdong Women and Children Hospital. Continuous variables were compared using the Mann–Whitney U test. Categorical variables were analyzed with the χ 2 test or Fisher's exact test, as appropriate. A receiver operating characteristic (ROC) curve was used to evaluate the predictive value of the LTLR for distinguishing PCP from other pathogen‐related pneumonia. Results Thirteen non‐HIV‐infected infants with PCP and 50 infants with viral or Mycoplasma pneumoniae pneumonia were enrolled. Compared with the control group, the PCP group had significantly greater rates of underlying conditions. Cytomegalovirus coinfection was more common in the PCP group. Laboratory findings revealed significantly lower white blood cell counts, total lymphocyte counts, and albumin levels, alongside elevated C‐reactive protein, lactate dehydrogenase, and LTLR in the PCP group. PCP patients also had higher rates of respiratory support, reinfection, and mortality, as well as longer hospital stays. LTLR was positively correlated with the length of hospital stay. ROC curve analysis revealed that the LTLR had an area under the curve (AUC) of 0.845 (95% CI: 0.715–0.974) for predicting PCP, with a sensitivity of 69.2% and specificity of 94.0% at a cutoff value of > 441.82. Conclusion Early diagnosis of PCP in infants is difficult. Infants with PCP are usually immunocompromised and prone to viral coinfection. LTLR shows promise as a predictive biomarker for PCP in non‐HIV‐infected infants.